Health and academic performance of university students: Direct and mediating effect of social capital - Mehreen Fatima; Muhammad Shafique (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
The purpose of this study is to study the impact of social capital on psycho-social health, psycho-social wellbeing and physical health of university students. The main focus is on the social correlates of psycho-social health, psycho-social wellbeing and physical health of students. This study is based on primary data that is collected from university students of a university. First, this study examines whether social capital affects different dimensions of health of university students. Second, it investigates whether any relationship exists between academic performance of university students and all other variables of the study. Third, it examines whether social capital mediates the relationship between different dimensions of health and academic performance of university students. Social capital is found to be significant for academic performance and it also mediates the relationship between academic performance and psycho-social health, psycho-social wellbeing and physical health.
Keywords: 330; social capital; neighborhood social capital; perceived social support; perceived stress; general social trust; psycho-social health; psycho-social wellbeing; physical health; satisfaction with life; subjective happiness